2015
DOI: 10.2214/ajr.14.13762
|View full text |Cite
|
Sign up to set email alerts
|

CT of Anatomic Variants of the Paranasal Sinuses and Nasal Cavity: Poor Correlation With Radiologically Significant Rhinosinusitis but Importance in Surgical Planning

Abstract: Analysis of every routine CT scan of the paranasal sinuses obtained for sinusitis or rhinitis for the presence of different anatomic variants is of questionable value unless surgery is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 20 publications
7
85
2
6
Order By: Relevance
“…It is also possible that patients with CT scans showing no or minimal evidence of sinus inflammation may have had significant sinusitis on previous CT scans that improved or resolved even though they continued to experience sinusitis symptoms. 6 To minimize such problems in the present study, the chronic sinusitis patients were given a course of antibiotics antihistaminics and nasal decongestants just before the CT scan study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is also possible that patients with CT scans showing no or minimal evidence of sinus inflammation may have had significant sinusitis on previous CT scans that improved or resolved even though they continued to experience sinusitis symptoms. 6 To minimize such problems in the present study, the chronic sinusitis patients were given a course of antibiotics antihistaminics and nasal decongestants just before the CT scan study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found wide variation (2-83%) in occurrence of agger nasi. [4][5][6]8 Studies demonstrate that their major dimensions are correlated with frontal sinus diseases and lacrimation. 7 All the subjects in the study had discharge in the frontal sinus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations